An investigation of the fluorescence emitted by arterial intimas during irradiation by a XeCl excimer laser - Bhagwandin, Niresh (Department of Human Biology, 2023)
Laser angioplasty of occluded arteries has been limited by the unacceptably high rate of vessel wall perforation. To overcome this limitation, fluorescence spectroscopy of arterial wall tissue has been proposed as a technique to discriminate between normal and atherosclerotic arteries and thereby prevent arterial wall perforation during laser angioplasty.